The Influence of Cultural Values and Norms on Political Attitudes and Behavior: A Sociological Study - Muhammad Touseef; Bedar Bakht Khan; Shahbaz Ali; Hasnain Nazar Abbas; Ahsan Raza (Advanced Qualitative Research, 2023)
This paper examines the complex interrelationship between cultural forces and political attitudes and behaviors. Through an extensive literature review, expert interviews, and rigorous content analysis, the research illuminates how cultural values, beliefs, and norms fundamentally shape individuals' political ideologies, policy preferences, partisan affiliations, civic engagement, and voting patterns. Findings demonstrate adherence to traditional cultural values like religiosity and nationalism predicts conservative political orientations, while progressive values like secularism and multiculturalism predict liberal orientations. The study also uncovers how politicians and media strategically exploit cultural symbols and narratives to frame issues and manipulate public opinion to their advantage. Prevailing cultural attitudes regarding duties and efficacy as citizens are shown to influence voter turnout and election outcomes. Promising reforms to address cultural biases include increasing access to diverse perspectives and critical civic education, promoting inclusive institutions and cross-cultural dialogue, and fostering political literacy. This research underscores the need for democratic processes and policies attuned to diverse cultural standpoints to pursue shared interests equitably. It concludes that comprehending the cultural antecedents of political behaviors and interpretations is essential for just, effective governance in pluralistic societies.